Reimagining the Sahn: Open Spaces and Universal Design Principles for Generation Z Inclusive Mosques - Achmad Delianur Nasution; Wahyuni Zahrah; Tri Febrianne Dhiyanthi; Nangkula Utaberta; Shafira Imanina (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2026)
Open spaces have been a key feature of mosques since the first Nabawiy Mosque was built during the time of the Prophet Muhammad. Fourteen centuries have passed, and mosques have evolved in accordance with their surroundings, with open spaces not always being a key feature of mosques. The issue of mosque designs that tend to be exclusive is an important reason for reviving the inclusive nature of mosques as in the time of the Prophet (peace be upon him). This paper aims to review the role of open spaces in mosques in meeting the needs of the wider community, including various age groups and socioeconomic strata, and even non-Muslims. This paper also puts forward an idea for integrating open spaces into mosque design for Generation Z. This generation, with its unique characteristics, is expected to play an increasingly important role in revitalizing mosques. This study adopts a mixed-methods research-by-design (RBD) framework, combining a qualitative historical and literature synthesis, exploratory precedent case studies, and a quantitative user preference survey involving 100 Muslim Generation Z respondents (N = 100) in Medan, Indonesia. The findings from these methods were integrated to formulate design ideas for inclusive mosque open spaces that respond to the needs and preferences of Generation Z. This study shows that open spaces are an important key feature for inclusive mosques that are in line with the needs of Generation Z, who are open-minded towards advances in information and developments in thought, art, science, and technology. The concept of inclusive mosque design for Generation Z offers open spaces that are integrated with urban spaces and directly connected to mosques structurally, functionally, and visually, where social activities become a showcase for mosque activities.